Review of Recent Crisis Programs. (Policy Papers; Policy Paper, 2009)
This study concludes that recent Fund-supported programs in emerging market countries are delivering the kind of policy response and financing needed to cushion the blow from the worst global crisis since the 1930s. While the crisis has had a profound effect on output and employment, especially in those countries starting with large external vulnerabilities, many of the severe disruptions attending previous crises-currency overshooting and bank runs-have so far been avoided. Internalizing lessons from the past, programs have responded to country conditions and adapted to worsening economic circumstances to attenuate contractionary forces. As a result, signs of stabilization are emerging in program countries, though there remain challenges to secure sustained recovery in a number of countries.